A TGF‐β1 genetic variant at the miRNA187 binding site significantly modifies risk of HPV16‐associated oropharyngeal cancer. Issue 6 (2nd May 2018) - Tao, Ye; Sturgis, Erich M.; Huang, Zhigang; Sun, Yan; Dahlstrom, Kristina R.; Wei, Qingyi; Li, Guojun
Abstract : TGF‐ β 1 rs1982073 polymorphism at the miRNA‐187 binding site may alter TGF‐β1 expression and function, and thereby this polymorphism (genotype CT/CC) increases cancer susceptibility. HPV16 L1 seropositivity is associated with the risk of oral squamous cell carcinoma (OSCC), including oropharyngeal squamous cell carcinoma (OPSCC) and oral cavity squamous cell carcinoma (OCSCC). Thus, we hypothesized that TGF‐ β 1 rs1982073 polymorphism at the miRNA‐187 binding site combined with HPV16 L1 seropositivity may have a joint effect on OSCC susceptibility. We determined the genotypes of TGF‐ β 1 rs1982073 and HPV16 status in 325 OSCC subjects and 335 cancer‐free controls in the non‐Hispanic white population, and used logistic regression models to evaluate the joint effects on OSCC susceptibility. TGF‐ β 1 rs1982073 polymorphism (CT/CC genotype) combined with HPV16 L1 seropositivity increased the risk of OSCC via joint effects, particularly in OPSCC subjects who were never‐smokers (OR, 165.9; 95% CI, 28.6–960.4) or never‐drinkers (OR, 196.0; 95% CI, 28.2–1, 000.0), respectively. Younger subjects had a higher risk of OPSCC than older subjects (OR, 23.5; 95% CI, 6.3–87.0 vs. OR, 6.0; 95% CI, 1.7–17.9, respectively). The significant associations between this polymorphism and HPV16‐associated OSCC and OPSCC were also observed. However, OCSCC subjects did not have similar results. Our findings suggest that the joint effects of TGF‐ β 1 rs1982073 and HPV16 L1 seropositivity can increase risk of HPV16‐associated oral cancer, particularly in OPSCC subjects who are never‐smokers, never‐drinkers and young. This result may help us understand the tumorigenesis process and improve early detection, which are critical for prevention and intervention strategies. However, larger studies are needed to validate our findings. Abstract : What's new? Polymorphisms of transforming growth factor beta (TGF‐β) and infection with high‐risk human papilloma virus (HPV) types individually modify cancer risk, but the combined effect of both is largely unknown. The authors determined the genotype of a specific TGF‐β1 variant that also affects the binding site of miRNA‐187 in patients with oral squamous cell carcinoma, a cancer often associated with HPV type 16 infection. They find that this variant combined with HPV16 seropositivity increased oral cancer susceptibility, particularly in young and risk‐free individuals, and propose that it could serve as a biomarker for risk of HPV16‐associated oral cancer.